Performance analysis of zero common‐mode voltage pulse‐width modulation techniques for three‐level neutral point clamped inverters. Issue 14 (1st November 2016) - Kai, Li; Zhao, Jiancheng; Wu, Wenjie; Li, Mengshu; Ma, Lan; Zhang, Gang
Abstract : This study surveyed three zero common‐mode voltage (CMV) pulse‐width modulation (PWM) methods for three‐phase three‐level neutral point clamped voltage source inverters, investigates their performance characteristics, and provides a comparison with the standard three‐level and two‐level space vector PWM methods. DC‐link voltage utilisation, harmonic distortion factor, DC‐link current ripple factor and power losses of each PWM method are thoroughly investigated by analysis, simulations and experiments. The research results illustrate the advantages and disadvantages of the compared methods and provide the basis for the selection and application of appropriate PWM methods in low CMV requirement fields.